Averaging principle for fractional heat equations driven by stochastic measures - Jiang-lun Wu (Applied Mathematics Letters, 2020)
In this paper, by utilising Besov space techniques, we establish the time averaging principle for a heat equation with fractional Laplace driven by a general stochastic measure $μ$ which is assumed (only) to satisfy the $σ$-additivity in probability.